Kinerja Perbankan Syariah di Indonesia Masa Pandemi Covid19 - Hananto, Bernad (DPPM Universitas Pelita Bangsa, 2022)
Social activity policies, in overcoming the Covid19 pandemic that hit the world, had an impact on economic activity in Indonesia, economic contraction had an impact on the business world in various sectors, one of which was the banking sector, therefore this research is to see the performance and growth of Islamic banking in Indonesia during the covid19 pandemic. This research is a quantitative study using Islamic banking statistics and a comparison of the pre-pandemic period with the COVID-19 pandemic, using the Paired two Sample for Mean Test. Research reveals that Islamic Banking did not experience significant obstacles during the COVID-19 pandemic, both in terms of Capital Adequacy Ratio (CAR), Liquidity, Asset Quality, Funding Portion, Rentabilitas and Profitability as well as growth, CAR experienced a significant increase, Non Performing Loans as well as Classified Earning Assets decreased/improved, the percentage of operating costs to operating income (BOPO) decreased/improved during the pandemic, but growth in Capital, Financing and also Operating Income during the The second year of the 2021 pandemic has a downward trend in average growth compared to the normal period and the first year of the pandemic.